Synthesis of Alginate-Chitosan Polyelectrolyte Complex (PEC) Membrane and Its Physical-Mechanical Properties - Dhony Hermanto; Mudasir Mudasir; Dwi Siswanta; Bambang Kuswandi (Jurnal Kimia Sains dan Aplikasi, 2019)
Synthesis of alginate-chitosan polyelectrolyte membrane and the determination of the physical-mechanical properties were carried out. Alginate-chitosan polyelectrolyte complex membrane can be made by mixing hydrosol alginate and chitosan hydrosol with a ratio of 1: 1 at pH 5.28. Membranes of alginate-chitosan polyelectrolyte complexes produced have physical-mechanical properties including load, elongation and elasticity, water absorption and resistance better than the constituent polymers. The results of FTIR spectroscopy analysis showed that there was an electrostatic interaction between alginate and chitosan through protonated amine groups of chitosan and carboxylic groups from alginate. Surface analyses by SEM showed that morphology of alginate-chitosan polyelectrolyte complex membrane was different with single membrane morphology